2011
DOI: 10.1016/j.bbamcr.2011.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Akt and FAK phosphorylation reduces invasion of glioblastoma cells by impairment of MT1-MMP shuttling to lamellipodia and downregulates MMPs expression

Abstract: Human malignant glioblastomas are highly invasive tumors. Increased cell motility and degradation of the surrounding extracellular matrix are essential for tumor invasion. PI3K/Akt signaling pathway emerges as a common pathway regulating cellular proliferation, migration and invasion; however, its contribution to particular process and downstream cascades remain poorly defined. We have previously demonstrated that Cyclosporin A (CsA) affects glioblastoma invasion in organotypic brain slices and tumorigenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 59 publications
8
38
0
Order By: Relevance
“…The results of the present study also indicated that in the early migration process, reduced expression of FAK significantly decreased the number of lamellipodia. This result is consistent with the results of a study by Kwiatkowska et al (15), which found that the decreased expression of phosphorylated FAK (phospho-FAK) suppressed the migration of malignant glioma cells. The study also revealed that lamellipodia formation was significantly prolonged in the cells with low levels of phospho-FAK.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the present study also indicated that in the early migration process, reduced expression of FAK significantly decreased the number of lamellipodia. This result is consistent with the results of a study by Kwiatkowska et al (15), which found that the decreased expression of phosphorylated FAK (phospho-FAK) suppressed the migration of malignant glioma cells. The study also revealed that lamellipodia formation was significantly prolonged in the cells with low levels of phospho-FAK.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have indicated that FAK may have a direct role in cell survival (63)(64)(65)(66); however, there are also published data showing that inhibition of the activation of FAK does not affect cell proliferation (16,(67)(68)(69). EcTI did not alter cell cycle progression (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…Actually these kinase signalings had been correlated with the increased invasiveness of glioblastoma cells (49,50). For example, the alteration of the IP3K/Akt pathway was reported to regulate the migration and invasion of human glioma cells LN229, T89G, and U-373 through the reduction of MMP-2 and MT1-MMP (43). NK1R activation was verified to induce MAPK and Akt activation, mediating cell proliferation and the anti-apoptosis effect in glioma cells and other tumor cells (15,16,21).…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase Reporter Assays for NF-B and AP-1 ActivityThe luciferase reporter gene assay was measured as described previously (38,43). Briefly, U-251 cells were seeded in a 60-mm dish to reach 80 -90% confluence overnight.…”
Section: Methodsmentioning
confidence: 99%